Rheumatoid Arthritis: Clinical-Laboratory and Ultrasound Parallels - I. A. Krivotulova; T. V. Chernysheva (Архивъ внутренней медицины, 2021)
Purpose. To establish the relationship of serum adiponectin and leptin with clinical data, serological parameters, disease activity, results of ultrasound examination of the musculoskeletal system and X-ray damage of joints in rheumatoid arthritis patients.Materials and methods. The article presents a comparative characteristic of adipokine levels among 64 women diagnosed with rheumatoid arthritis (group I) and 30 healthy women (group II). The dependence of adipokine levels on clinical, laboratory, ultrasound and radiological changes was revealed in patients with rheumatoid arthritis.Results. The concentration adiponectin level was significantly higher in rheumatoid arthritis patients compared to the control group (p <0.0001) and had significant correlations with radiological changes in the joints (r=0.40; p <0.001) and the intake duration of methotrexate (r=0.4; p <0.001) and glucocorticosteroids (r=0.3; p <0.05). The level of leptin in the blood serum of women with rheumatoid arthritis and healthy individuals was approximately the same. However, there were positive correlations between the level of leptin and of the tender joint count (r=0.5; p <0.0001), the levels of C-reactive protein (r=0.3; p <0.05) and interleukin-17 (r=0.3; p <0.05), the index Disease Activity Score 28 (r=0.4; p <0.001) and increased blood flow during Doppler imaging (r=0.4; p <0.001).Conclusion. Thus, patients with rheumatoid arthritis have a significant increase in the level of adiponectin compared to the health group, which is associated with pronounced destructive changes in the joints and the intake duration of methotrexate and glucocorticosteroids. However, a positive relationship between the indicators of disease activity and the presence of a Doppler signal is observed only in leptin.